2018
DOI: 10.1038/s41598-018-26097-x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in T cell effector functions over an 8-year period with TNF antagonists in patients with chronic inflammatory rheumatic diseases

Abstract: The aim of the study was to clarify the effect of long-term anti-TNF therapy on T cell function in patients with rheumatologic immune-mediated inflammatory diseases (IMID). The production of IFNγ by T cells was evaluated at baseline and after 1, 2, 4, and 8 years of anti-TNF agents by means of a QuantiFERON-TB Gold In-Tube assay. The T cell proliferation and surface co-expression of CD25/CD134 in response to phytohaemagglutinin together with the in vitro impact of anti-TNF therapy on the functional capacity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 42 publications
(42 reference statements)
0
12
0
Order By: Relevance
“…The study discovered that over these years, there were fluctuations in the production of IFN-γ, with the lowest levels in the first dose and after four years of use, while the doses after one, two, and eight years were even larger than the initial one, and there were no differences between the production of this cytokine in the two TNF blockers evaluated, namely etanercept and adalimumab, or between the two diseases, rheumatoid and psoriatic arthritis. It is also interesting to note that after these individuals used these immunobiologicals for eight years, no statistical differences were found in the production of IFN-γ in them when compared to healthy donors [ 50 ]; this is similar to our study, which also did not find differences in the production of any of the analyzed cytokines, IL-2, IFN-γ, IL-6, TNF-α, IL-4, IL-10, and IL-17, in the supernatant in IB and SD groups when compared to the CG, neither in the stimulation with the mitogen nor in the stimulus with T. gondii antigen.…”
Section: Discussionmentioning
confidence: 99%
“…The study discovered that over these years, there were fluctuations in the production of IFN-γ, with the lowest levels in the first dose and after four years of use, while the doses after one, two, and eight years were even larger than the initial one, and there were no differences between the production of this cytokine in the two TNF blockers evaluated, namely etanercept and adalimumab, or between the two diseases, rheumatoid and psoriatic arthritis. It is also interesting to note that after these individuals used these immunobiologicals for eight years, no statistical differences were found in the production of IFN-γ in them when compared to healthy donors [ 50 ]; this is similar to our study, which also did not find differences in the production of any of the analyzed cytokines, IL-2, IFN-γ, IL-6, TNF-α, IL-4, IL-10, and IL-17, in the supernatant in IB and SD groups when compared to the CG, neither in the stimulation with the mitogen nor in the stimulus with T. gondii antigen.…”
Section: Discussionmentioning
confidence: 99%
“…Martyn‐Simmons et al 21 reported the absence of a strong association between concomitant immunosuppression, and QFT positivity; however, Tavast et al 22 studied 109 patients (21 with psoriasis, 74 with inflammatory musculoskeletal diseases, and 14 other inflammatory conditions) and found that immunosuppression adversely affected the TST but not QFT. Sauzullo et al 23 revealed that in vitro addition of TNF‐α inhibitors lead a significant decrease of IFNγ response in patients with chronic rheumatic diseases. A meta‐analysis showed that interferon γ release assay (IGRA) results are negatively affected by immunosuppressive therapy, and IGRA alone may not be sufficiently sensitive to diagnose LTBI in patients on immunosuppressive therapy.…”
Section: Discussionmentioning
confidence: 99%
“…TST but not QFT. Sauzullo et al23 revealed that in vitro addition of TNF-α inhibitors lead a significant decrease of IFNγ response in patients with chronic rheumatic diseases. A meta-analysis showed that interferon γ release assay (IGRA) results are negatively affected by immunosuppressive therapy, and IGRA alone may not be sufficiently sensitive to diagnose LTBI in patients on immunosuppressive therapy.…”
mentioning
confidence: 99%
“…TNF-α inhibitors can counteract the entire disease process in patients with chronic inflammatory diseases (e.g., RA, psoriatic arthritis (PsA), CD, and ulcerative colitis (UC)) by fundamentally modulating the molecular and cellular changes of several inflammatory networks of the innate immune system [6,10,16,17,[29][30][31]. The focus is on the reduction of Furthermore, chronic inflammatory processes, and specifically the concentration of TNF-α, drive cardiovascular events, such as atherosclerosis, atherothrombotic disease, and venous thromboembolism [27].…”
Section: Tnf-α Inhibitor Therapy Restores Cytokine Balance and Normal...mentioning
confidence: 99%